2020
DOI: 10.1371/journal.pone.0227055
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of Leptospira in water and soil environments

Abstract: Background Leptospirosis, caused by pathogenic Leptospira, is a zoonosis of global distribution. This infectious disease is mainly transmitted by indirect exposure to urine of asymptomatic animals via the environment. As human cases generally occur after heavy rain, an emerging hypothesis suggests that rainfall re-suspend leptospires together with soil particles. Bacteria are then carried to surface water, where humans get exposed. It is currently assumed that pathogenic leptospires can survive in the environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
176
1
7

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(192 citation statements)
references
References 113 publications
(176 reference statements)
8
176
1
7
Order By: Relevance
“…The fact that most of the patients in our sample set (83%) were males corresponds well with the findings of many other epidemiological studies, where males were found to be the major victims of this pathogen [3,6]. In addition, leptospirosis is known to be seasonal, and strongly associated with rainfalls in tropical settings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The fact that most of the patients in our sample set (83%) were males corresponds well with the findings of many other epidemiological studies, where males were found to be the major victims of this pathogen [3,6]. In addition, leptospirosis is known to be seasonal, and strongly associated with rainfalls in tropical settings.…”
Section: Discussionsupporting
confidence: 90%
“…can colonize the renal tubules of a wide variety of wild and domesticated mammals. The bacteria are shed in the urine of infected animals and persist in freshwater [3]. Transmission to a new host usually occurs after exposure to this contaminated water [4].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it appears that heavy rainfall increases the chance of surface water contamination of Leptospira from the urine of carrier animals such as rats, mongoose, and other animals in Puerto Rico. It is assumed that rainfall can resuspend and transport Leptospira attached to soil particles into rivers and streams (Bierque et al, 2020). These findings are supported by several studies that have reported outbreaks of Leptospirosis after heavy rainfall and flooding events (Goarant et al, 2009;Sharp et al, 2016;Smith et al, 2013).…”
Section: Resultsmentioning
confidence: 73%
“…The bacterium can survive for about a week in moist soil and mud when temperature and other conditions are favorable [ 3 ], although Thibeaux et al (2017) [ 16 ] found that pathogenic leptospires remained viable in soils for several weeks under laboratory conditions. Emerging evidence also supports the hypothesis that rainfalls re-suspend Leptospira with soil particles, which are carried to surface water, where animals and humans get exposed [ 17 ].…”
Section: Introductionmentioning
confidence: 62%